2019
DOI: 10.1177/0361198119846479
|View full text |Cite
|
Sign up to set email alerts
|

Safety Assessment of Two-Lane Highway using a Combined Proactive and Reactive Approach: Case Study from Indian National Highways

Abstract: In India, approximately 30% of road accident fatalities occur on two-lane rural roads. Thus research focused on identifying risk factors on this road type is of immense interest to most of the road agencies. Although these highways are more hazardous and account for more severe crashes, there is a lack of scientific safety assessment of such highways compared with multi-lane highways. Proactive approaches, such as road safety audit, have been widely adopted by the government of India to reduce crash frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…In this regard, a comprehensive list of suitable countermeasures is provided in Table 5 with details of where and how they could be used. These recommended countermeasures are adopted worldwide for reducing ROR crash severity ( 31 , 38 , 39 , 41 ) and can be used alone or in a package to treat locations with unsafe roadside condition. For example, a long monotonous road stretch with dense trees along should be treated with demarcation as well as edge/shoulder rumble strips.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, a comprehensive list of suitable countermeasures is provided in Table 5 with details of where and how they could be used. These recommended countermeasures are adopted worldwide for reducing ROR crash severity ( 31 , 38 , 39 , 41 ) and can be used alone or in a package to treat locations with unsafe roadside condition. For example, a long monotonous road stretch with dense trees along should be treated with demarcation as well as edge/shoulder rumble strips.…”
Section: Resultsmentioning
confidence: 99%
“…Such poor quality of crash data often causes a hindrance in estimating the impact of roadside conditions on safety performance, in regard to crash occurrence and outcome through statistical modelling. In such cases, often the combination of the limited information available from the crash reports (reactive) and safety inspection of crash sites (proactive) can be effectively utilized to identify safety issues and roadside risk factors along the road network ( 31 ). Keeping that in mind, the study methodology is based on a combined reactive–proactive approach as shown in Figure 1.…”
Section: Study Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Road traffic crashes are complex events that are difficult to predict due to the fact that their constituent causes generally include a combination of several interrelated factors including the geometric design of the road, vehicle and environmental factors, and driver behaviour and perceptions (Fitzpatrick 2014;Turner et al 2015;Ambunda & Sinclair 2019;Chatterjee & Mitra 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Most often a driver responds to a road environment based on the messages that he or she 'reads' from the roadway conditions (Bester & Makunje 1998;Ambunda & Sinclair 2019). These may include -but are not limited to -components of road geometry, road surface and traffic characteristics relating to traffic composition and speed (Fitzpatrick 2014;Ambunda & Sinclair 2019;Chatterjee & Mitra 2019). The response of drivers to individual elements is shaped by a number of things, including (among others) their age and driving experience, the cognitive load placed on them at the time, their stimulusresponse compatibility (largely determined by previous exposure to the particular road element); and their prior expectations (Vaa 2014;Bongiorno et al 2017).…”
Section: Introductionmentioning
confidence: 99%